Análise da percepção ambiental de alunos do ensino médio de uma escola estadual no município de Capinzal, SC - Bressan, Ana Paula (2015)
This work had as thematic, the study of environmental perception with high school students, in such case, the school is one of the ways which directs the development of the citizen into the society, this research provides the acquisition of the important and the needful data for the Environmental Education, it also helps in the search of the measures and strategies to be achieved inside the Environmental Management, thinking in the awareness of society and the development in favor of the environment. The study aims to verify the students opinions about the environmental questions, realizing thus, the environmental perception of itself, so that to collect important information for the Environmental Education and school totality. The used methodology was based in means of the collect of questionnaire with open and closed question, and the same was applied for a whole of 100 students registered in high schools of the searched school. With the review of the data, it was verified that the studies have a notable environmental perception in relation to the local which they are inserted to, although many times, their attitudes don’t contribute meaningly for the conservation and the preservation of the middle of the live in, there is the necessary to go on, with a greater intensity of the activities turned with the care with the environment and the environmental problems.